Screening for the Genes Involved in Bombykol Biosynthesis: Identification and Functional Characterization of Bombyx mori Acyl Carrier Protein - Ohnishi, Atsushi; Kaji, Misato; Hashimoto, Kana; Matsumoto, Shogo (Frontiers in Endocrinology, 2011)
Species-specific sex pheromones released by female moths to attract conspecific male moths are synthesized de novo in the pheromone gland (PG) via fatty acid synthesis (FAS). Biosynthesis of moth sex pheromones is usually regulated by a neurohormone termed pheromone biosynthesis activating neuropeptide (PBAN), a 33-aa peptide that originates in the subesophageal ganglion. In the silkmoth, Bombyx mori, cytoplasmic lipid droplets (LDs), which store the sex pheromone (bombykol) precursor fatty acid, accumulate in PG cells prior to eclosion. PBAN activation of the PBAN receptor stimulates lipolysis of the stored LD triacylglycerols (TAGs) resulting in release of the bombykol precursor for final modification. While we have previously characterized a number of molecules involved in bombykol biosynthesis, little is known about the mechanisms of PBAN signaling that regulate the TAG lipolysis in PG cells. In the current study, we sought to further identify genes involved in bombykol biosynthesis as well as PBAN signaling, by using a subset of 312 expressed sequence tag (EST) clones that are in either our B. mori PG cDNA library or the public B. mori EST databases, SilkBase and CYBERGATE, and which are preferentially expressed in the PG. Using RT-PCR expression analysis and an RNAi screening approach, we have identified another 8 EST clones involved in bombykol biosynthesis. Furthermore, we have determined the functional role of a clone designated BmACP that encodes B. mori acyl carrier protein (ACP). Our results indicate that BmACP plays an essential role in the biosynthesis of the bombykol precursor fatty acid via the canonical FAS pathway during pheromonogenesis.